Improving nutritional status among urban poor children in sub‐Saharan Africa: An evidence‐informed Delphi‐based consultation - Maurice Mutisya; Oonagh Markey; Emily K. Rousham; Jesman M. N. Chintsanya; Rebecca Pradeilles; Elizabeth W. Kimani‐Murage; Nyovani J. Madise; Alister C. Munthali; Alexander Kalimbira; Michelle Holdsworth; Paula L. Griffiths; Emma Haycraft (Wiley, 2021)
Abstract In sub‐Saharan Africa (SSA), rapid urbanisation coupled with the high prevalence of infant and young child (IYC) undernutrition in low‐income settings means that interventions to support IYC nutrition are a priority. Little is known about how urbanisation influences IYC feeding (IYCF) practices, and evidence‐based interventions to improve IYC health/nutrition in the urban poor are lacking. Therefore, this research aimed to (a) systematically review evidence on interventions for improving the nutritional status of IYC aged 6-23 months living in urban poor areas (PROSPERO CRD42018091265) and (b) engage stakeholders to identify the highest ranking evidence gaps for improving IYCF programmes/policies. First, a rapid systematic review was conducted. This focused on the literature published regarding nutrition‐specific and nutrition‐sensitive complementary feeding interventions in urban poor areas, specifically low‐income informal settlements, in low‐ and middle‐income countries (LMICs). Six intervention studies met the review inclusion criteria. Intervention adherence was generally high, and indicators of maternal knowledge and IYC nutritional intake typically increased because of the interventions, but the impact on anthropometric status was small. Second, stakeholders working across SSA were engaged via a Delphi‐based approach to identify priority areas for future intervention. Stakeholders reported that a situational analysis was required to better understand IYCF in urban poor areas, particularly the causes of IYC undernutrition, and highlighted the need to involve local communities in defining how future work should proceed. Together, these findings indicate a need for more evidence regarding IYCF and the factors that drive it in urban poor areas across LMIC settings, but particularly in SSA.